Prevalence of Taenia Species among Cattle Slaughtered in Oye Local Government Area, Ekiti State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
This study investigates the prevalence of Taenia species among cattle slaughtered in Oye, Ekiti State. Taenia poses a zoonotic threat through the consumption of undercooked or contaminated beef. The research was carried out through field sampling and in selected abattoirs across the study area, where infected tissues were screened for the presence of cystic stages of Taenia Spp. Standard diagnostic approaches, including visual meat inspection and parasitological identification techniques, was used to detect and classify parasite present. In addition to assessing prevalence, the study considered patterns of co-infection with other gastrointestinal parasites and the role of environmental factors such as slaughter hygiene, animal sourcing, and grazing practices in disease transmission. Overall, 20% of the cattle were infected, with females showing a higher prevalence (12%) compared to males (8%). Infection rates varied by location, with Irare and Oye-Egbo recording equal infections (8%) and SY8 a lower rate (4%). The findings highlight the ongoing public health risks posed by parasitic infections in livestock, particularly in areas where meat inspection procedures are inconsistent or poorly enforced. This research underscores the need for improved veterinary services, routine screening, and health education targeting livestock handlers, butchers, and consumers. It also supports the implementation of stronger food safety policies under a One Health framework, considering the interconnectedness of human, animal, and environmental health. By providing data on the parasitic status of slaughtered cattle in Oye, this study contributes to the broader understanding of zoonotic disease dynamics in southwestern Nigeria and informs future strategies for management.